Monolithic stirrer reactor for vegetable oil hydrogenation: A technical and economic assessment - Boldrini, Diego Emmanuel (2018)
The monolithic stirrer reactor (MSR) which consists on monolithic structures mounted on reactor axis as agitator blades is a novel design with the potential to intensify different production processes. Its most outstanding advantages are the absence of a filtering stage after the reaction and the high-speed mass transfer. In this paper, the technical and economic feasibility of sunflower oil hydrogenation process under MSR (Pd/Al2O3/Al) configuration was studied considering a 100 ton day-1 productive plant, a 20 ton capacity reactor and a final product with 75 iodine index. Moreover, several reaction conditions were taken into account, such as catalyst loading and initial and final reaction temperatures, in order to determine the operating costs. The proposed alternative process could be profitable, displaying a higher Net Present Value (NPV) than the conventional technology one. However, slight variations in the monolithic catalyst cost performed through a sensitivity analysis generate a considerable decrease in NPV, thus determining that the implementation of the proposed alternative technology presents a high economic risk. The achieved results in this study indicate that further research is necessary in order to develop a regenerating procedure to extend the catalyst useful life, thus favouring the monolithic technology economy.